Standardising surveillance of hepatitis E virus infection in the EU/EEA: A review of national practices and suggestions for the way forward - Adlhoch, Cornelia; Manďáková, Zdenka; Ethelberg, Steen; Epštein, Jevgenia; Rimhanen-Finne, Ruska; Figoni, Julie; Baylis, Sally A; Faber, Mirko; Mellou, Kassiani; Murphy, Niamh; O'Gorman, Joanne; Tosti, Maria Elena; et al. (Journal of clinical virology, 2019)
BACKGROUND: Hepatitis E virus (HEV) infection is not notifiable at EU/EEA level, therefore surveillance relies on national policies only. Between 2005 and 2015, more than 20,000 cases were reported in EU/EEA countries. HEV testing is established in 26 countries and 19 countries sequence HEV viruses. OBJECTIVE AND STUDY DESIGN: WHO's European Action plan for viral hepatitis recommends harmonised surveillance objectives and case definitions. ECDC's HEV expert group developed minimal and optimal criteria for national hepatitis E surveillance to support EU/EEA countries in enhancing their capacity and to harmonise methods. RESULTS: The experts agreed that the primary objectives of national surveillance for HEV infections should focus on the basic epidemiology of the disease: to monitor the incidence of acute cases and chronic infections. The secondary objectives should be to describe viral phylotypes or subtypes and to identify potential clusters/outbreaks and possible routes of transmission. Seventeen of 20 countries with existing surveillance systems collect the minimal data set required to describe the epidemiology of acute cases. Eleven countries test for chronic infections. Twelve countries collect data to identify potential clusters/outbreaks and information on possible routes of transmission. DISCUSSION: Overall, the majority of EU/EEA countries collect the suggested data and meet the outlined requirements to confirm an acute case.
Keywords: Evropská unie; EU/EEA; Government Programs; Population Surveillance; Europe; Incidence; European Union; Evropa; Hepatitis E; Světová zdravotnická organizace; Disease Outbreaks; incidence; RNA, Viral; World Health Organization; surveillance populace; Testing; hepatitida E; epidemický výskyt choroby; Hepatitis E virus; Humans; epidemiologické monitorování; vládní programy; virus hepatitidy E; Epidemiological Monitoring; RNA virová; lidé; Surveillance